2011
DOI: 10.1590/s0100-204x2011000500013
|View full text |Cite
|
Sign up to set email alerts
|

Bioindicators of soil quality in coffee organic cultivation systems

Abstract: -The objective of this work was to assess the effect of different coffee organic cultivation systems on chemical and biological soil characteristics, in different seasons of the year. The following systems were evaluated: coffee intercropped with one (CJ1), two (CJ2) or three (CJ3) pigeon pea (Cajanus cajan) alleys; coffee planted under full sun (CS); area planted with sweet pepper and snap bean in a conventional tillage system (AC); and secondary forest area (FFR). Row spacing in CJ1, CJ2, CJ3 and CS was 2.0x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…The available phosphorus showed the highest value in the cluster with agroforestry-based coffee and corresponds with the research which found that the phosphorus content was higher in the coffee under organic rather than conventional management (Tully et al, 2013). Agroforestry-based coffee is most commonly cultivated to cope with the physiological stress, decreased soil erosion and to generate additional income for the farmer (Pimentel et al, 2011;Tscharntke et al, 2011).…”
Section: Pca Mds and Sqi Clusteringsupporting
confidence: 82%
“…The available phosphorus showed the highest value in the cluster with agroforestry-based coffee and corresponds with the research which found that the phosphorus content was higher in the coffee under organic rather than conventional management (Tully et al, 2013). Agroforestry-based coffee is most commonly cultivated to cope with the physiological stress, decreased soil erosion and to generate additional income for the farmer (Pimentel et al, 2011;Tscharntke et al, 2011).…”
Section: Pca Mds and Sqi Clusteringsupporting
confidence: 82%
“…In OS, we found a greater density of soil macrofauna in winter, a result that differs from most references in the literature, where the normal is to find a greater density in summer. Pimentel et al (2011) report a greater density in coffee plantations in summer, while Fernandes et al (2013) highlight a greater mobility of soil fauna in coffee plantations in the rainy season. Silva et al (2012) mention that summer is more adequate for reproduction, resulting in a greater numbers of soil fauna community, so that most authors disagree from our results.…”
Section: Macrofaunamentioning
confidence: 99%
“…Analogamente, a manutenção da cobertura vegetal na superfície do solo pode favorecer a atividade dos organismos engenheiros do ecossistema e promover maior diversidade de macrofauna. Pimentel et al (2011), ao estudarem o efeito de consórcios de diferentes espécies com cafeeiro observaram também maior abundância dos grupos Coleoptera, Formicidae e Isoptera em sistemas consorciados com guandu quando comparados ao sistema convencional, resultado associado à presença de camada herbácea e maior disponibilidade de alimentos à macrofauna.…”
Section: Resultsunclassified
“…Fitomassas heterogêneas (incluindo a serapilheira e plantas daninhas) presentes em SAFs, além de contribuírem para melhoria da fertilidade do solo (Carmo et al, 2014;Guimarães et al, 2014;LOPES et al, 2014), ampliam as condições para a ocorrência de um maior número de espécies de fauna pela grande disponibilidade de recursos e microhábitats, permitindo o desenvolvimento de organismos dos mais diversos tamanhos e grupos funcionais, como a fauna edáfica (Souto et al, 2008;Lima et al, 2010;Pimentel et al, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation